Prevalence of Consumers Purchasing Antibiotic Medicine Without Prescription Among Community Pharmacies - Garcia, Ronnel; Tugna, Claudette (Journal of Interdisciplinary Perspectives, 2024)
According to the Global Research on Antimicrobial Resistance, the Philippines has an average antibiotic use of 5.3 DDDs per 1,000 people, with pediatric antibiotic use constituting approximately 56.2%. Although lower than in neighboring countries, this level of use still poses a significant threat to the healthcare system. The widespread availability of antibiotics has been a major contributing factor to the rise of antibiotic resistance (ABR) in the Philippines. Historically, antibiotics could be purchased without a prescription from local pharmacies. This study examined the prevalence of consumers attempting to purchase antibiotics without a prescription in Carmona, Cavite. Utilizing quantitative descriptive and correlational research methodologies, the study employed convenience sampling due to the limited number of community pharmacies and their tendency to cluster in specific areas. A structured survey questionnaire was used to gather data and analyze correlations between variables. Findings indicate that the majority of consumers in Carmona, Cavite, frequently attempt to obtain antibiotics without a prescription, with a preference for penicillin-class antibiotics. The reasons for these purchases vary, including self-medication for minor illnesses, treatment for pets and poultry, and topical wound care. The results underscore the importance of community education and engagement on the risks of ABR. The study suggests that local government educational programs can enhance consumer awareness of the need for prescriptions. The findings indicate that awareness of prescription requirements moderately affects the frequency of attempting to buy antibiotics without a prescription. However, no significant association was found between the reasons for obtaining medicine without a prescription and the type or class of medicine purchased.